2011
DOI: 10.1002/alr.20091
|View full text |Cite
|
Sign up to set email alerts
|

Case report of orbital violation with placement of ethmoid drug‐eluting stent

Abstract: This is the first reported case of orbital violation with placement of an ethmoid drug-eluting stent. The literature shows feasibility in cadaveric studies but the practitioner must be diligent in placement. Ethmoid sinus stenting is an option for topical treatment of ethmoid sinusitis but practitioners must be cognizant of potential risks when counseling patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…1312,1313 There has also been a case report of orbital violation leading to pain and a permanently dilated pupil. 1314 Biodegradable drug-eluting stents offer the benefit of having both a mechanical spacer combined with precise sustained release of medication into the sinus cavity over a known period of time. 1315 Unlike nonbiodegradable stents, they may not require potentially painful postoperative removal.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…1312,1313 There has also been a case report of orbital violation leading to pain and a permanently dilated pupil. 1314 Biodegradable drug-eluting stents offer the benefit of having both a mechanical spacer combined with precise sustained release of medication into the sinus cavity over a known period of time. 1315 Unlike nonbiodegradable stents, they may not require potentially painful postoperative removal.…”
Section: Xd6 Surgical Principles/techniques: Drug Eluting Packingmentioning
confidence: 99%
“…Despite the eventual removal of the device, the patient's pupil remained dilated in the affected eye. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The SEI also compares favourably when assessing improvement in patient symptoms (a -29.7 change in baseline RSDI score using the Propel implant [25] compared with a change of -19.1 in other studies not using an SEI) [31]. Villari et al [32] reported a case of orbital violation due to a Strutus Ethmoid nonabsorbable sinus implant (Acclarent, Inc., Menlo Park, California, USA) resulting in severe orbital pain and a permanently dilated pupil. Occasional complications have been reported from the use of other sinus implants.…”
Section: Key Pointsmentioning
confidence: 99%